1992
DOI: 10.1016/0735-1097(92)90367-v
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive definition of anatomic coronary artery disease by ultrafast computed tomographic scanning: A quantitative pathologic comparison study

Abstract: The detection of coronary calcification by ultrafast computed tomographic scanning is highly predictive of the presence of histopathologic coronary disease, but the use of this technique to define the extent of coronary disease may be limited. However, the absence of coronary calcification at any site is highly specific for the absence of obstructive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
2
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(114 citation statements)
references
References 14 publications
3
106
2
3
Order By: Relevance
“…The absence of calcification, however, did correlate with the absence of advanced luminal disease on a site-by-site basis. A previous study by Simons and coworkers 27 determined that coronary calcification demonstrated on EBCT was present in 97.5% of all coronary segments with "significant" histologic coronary disease (that is, 75% or greater area or approximately a 50% or greater diameter stenosis).…”
Section: Coronary Calcium and Luminal Disease Severitymentioning
confidence: 99%
“…The absence of calcification, however, did correlate with the absence of advanced luminal disease on a site-by-site basis. A previous study by Simons and coworkers 27 determined that coronary calcification demonstrated on EBCT was present in 97.5% of all coronary segments with "significant" histologic coronary disease (that is, 75% or greater area or approximately a 50% or greater diameter stenosis).…”
Section: Coronary Calcium and Luminal Disease Severitymentioning
confidence: 99%
“…Coronary artery calcification as presently imaged is not a reliable indicator of atherosclerosis. 81 Furthermore, this technique has limited capability in measuring extent of coronary artery atherosclerosis. These major issues limit the usefulness of this noninvasive technique for clinical trials.…”
Section: Noninvasive Imaging Of the Coronary Arteriesmentioning
confidence: 99%
“…Coronary artery calcification (CAC) is highly correlated with the presence of coronary atherosclerotic plaque. [13][14][15] However, information on the association between CAC scores and UAE is currently limited.This study examined the association between UAE and several measures of subclinical CVD, including CAC scores, in a large multi-ethnic population without clinical CVD. We hypothesized that increased UAE is associated with subclinical CVD reflecting kidney damage caused by exposure to CVD risk factors, particularly diabetes mellitus (DM) and hypertension, and that these associations exist at UAE cutpoints below thresholds currently used to define microalbuminuria.…”
mentioning
confidence: 99%